NBD-based fluorescent probes for separate detection of cysteine and biothiols via different reactivities. Issue 21 (18th May 2020) - Huang, Haojie; Ji, Xiuru; Jiang, Yaqing; Zhang, Changyu; Kang, Xueying; Zhu, Jiqin; Sun, Lu; Yi, Long
Abstract : A NBD-based fluorescent probe is developed to seperately detect Cys and all biothiols via different reactivity. Abstract : NBD-based fluorescent probes that can separately detect cysteine and biothiols via different reactivities have been rationally designed and synthesized. The probes can be applied to kinetically distinguish cysteine from other biothiols at 30 min, and to detect all biothiols at 3 h in living cells.